Strategic Management of Islamic Boarding Schools in Preventing Students’ Bullying at Nawwarul Uyun NW Serumbung Islamic Boarding School - Muhamad Zaril Gapari; Abdurrahim; Ahmad Izzudin; Umar Bakri (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to analyze the strategic management implemented by Nawwarul Uyun NW Serumbung Islamic Boarding School in preventing bullying behavior within the boarding school environment. Bullying, whether physical, verbal, or non-verbal, is a serious challenge that can disrupt the spiritual and social development of students. Using a qualitative approach through a case study method, data were collected through interviews, observation, and documentation. The results show that the Islamic boarding school implements bullying-prevention strategies that include formulating internal policies, strengthening character education, employing persuasive approaches by teachers and caregivers, actively involving students in creating a positive environment, and conducting routine evaluations. These strategies are proven effective in building a safe educational climate that supports students’ personality development. This study recommends strengthening synergy among the islamic boarding school, parents, and the community to comprehensively address bullying.